Migration of RDBs into ORDBs and XML Data - Elbekai, Ali; Goweder, Abduelbaset; Shuwehdi, Abdulhafid (The Libyan Journal of Science, 2018)
XML and relational database are two of the most important mechanisms for storing and transferring data. A reliable and flexible way of moving data between them is a very desirable goal. The way data is stored in each method is very different which makes the translation process difficult. To try and abstract some of the differences away, a low– level common data model can be used to successfully move data from one model to the other. A way of describing the schema is needed. To the best of our knowledge, there is no widely accepted way of doing this for XML. Recently, XML Schema has taken on this role. On one hand, this study takes XML conforming to XML schema definitions and transforms them into relational database via the low–level modeling language HDM. On the other hand, a relational database is transformed into an XML Schema document and an XML instance document containing the data from the database. The transformations are done within the Auto med framework providing a sound theoretical basis for this work. A visual tool that represents the XML Schema in tree structure and allows some manipulation of the schema is also described.